New Gateway-compatible vectors for a high-throughput protein–protein interaction analysis by a bimolecular fluorescence complementation (BiFC) assay in plants and their application to a plant clathrin structure analysis. Issue 12 (2nd December 2015) - Nishimura, Kohji; Ishikawa, Syouta; Matsunami, Erika; Yamauchi, Junji; Homma, Keiichi; Faulkner, Christine; Oparka, Karl; Jisaka, Mitsuo; Nagaya, Tsutomu; Yokota, Kazushige; Nakagawa, Tsuyoshi
Abstract: Protein–protein interactions (PPI) play key roles in various biological processes. The bimolecular fluorescence complementation (BiFC) assay is an excellent tool for routine PPI analyses in living cells. We developed new Gateway vectors for a high-throughput BiFC analysis of plants, adopting a monomeric Venus split just after the tenth β-strand, and analyzed the interaction between Arabidopsis thaliana coated vesicle coatmers, the clathrin heavy chain (CHC), and the clathrin light chain (CLC). In competitive BiFC tests, CLC interacted with CHC through a coiled-coil motif in the middle section of CLC. R1340, R1448, and K1512 in CHC and W94 in CLC are potentially key amino acids underlying the inter-chain interaction, consistent with analyses based on homology modeling. Our Gateway BiFC system, the V10-BiFC system, provides a useful tool for a PPI analysis in living plant cells. The CLC–CHC interaction identified may facilitate clathrin triskelion assembly needed for cage formation. Graphical abstract: :